2015
DOI: 10.1016/j.ccell.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

A Tumor Suppressor Function for Notch Signaling in Forebrain Tumor Subtypes

Abstract: In the brain, Notch signaling maintains normal neural stem cells, but also brain cancer stem cells, indicating an oncogenic role. Here, we identify an unexpected tumor suppressor function for Notch in forebrain tumor subtypes. Genetic inactivation of RBP-Jκ, a key Notch mediator, or Notch1 and Notch2 receptors accelerates PDGF-driven glioma growth in mice. Conversely, genetic activation of the Notch pathway reduces glioma growth and increases survival. In humans, high Notch activity strongly correlates with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 58 publications
16
95
0
Order By: Relevance
“…If so, proliferative heterogeneity within the tumor hierarchy may reflect aspects of a conserved developmental mechanism. A similar parallel was also suggested in low-grade glioma (Giachino et al, 2015), where Notch signaling may promote a less aggressive, slow-cycling population, suggestive of a tumor suppressor role. Yet in the context of drug treatment, this promotion of a slow-cycling state may have the untoward consequence of conferring resistance.…”
Section: Discussionsupporting
confidence: 64%
“…If so, proliferative heterogeneity within the tumor hierarchy may reflect aspects of a conserved developmental mechanism. A similar parallel was also suggested in low-grade glioma (Giachino et al, 2015), where Notch signaling may promote a less aggressive, slow-cycling population, suggestive of a tumor suppressor role. Yet in the context of drug treatment, this promotion of a slow-cycling state may have the untoward consequence of conferring resistance.…”
Section: Discussionsupporting
confidence: 64%
“…The aberrant activation of notch signaling pathway may contribute to development of some tumors including melanoma, glioma, breast carcinoma, colon carcinoma, cervical cancer and so on [30, 31]. But it is also reported that notch signaling may serve as a suppressor in a few tumors, for example, forebrain tumor subtypes [22]. Therefore, the special roles of notch pathway in development of tumor may depend upon tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggest that notch pathway may promote the proliferation, survival, self-renewal, differentiation, angiogenesis, and migration of CSCs in several malignancies [1921]. It is worth to pay attention to that the notch pathway may play either an oncogenic role or a suppressor in tumor development based on the special tumor cell context [22]. Although RCC CSCs have been identified, the expression profile of notch pathway in RCC CSCs and whether it involves maintaining the stemness of RCC CSCs and the potential molecular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of both Notch and miR-9 in brain tumors is surprisingly complex. While Notch1 has been shown to be critical for proliferation and survival of glioma cells, 49 it was also proposed that Notch cooperates with p53 to keep NSCs in a state of quiescence preventing them from entering a state of fast division 50 . In this context, Notch signaling has a tumor-suppressive function, and its inactivation accelerates the growth of mouse gliomas.…”
Section: Introductionmentioning
confidence: 99%